1980
DOI: 10.2466/pms.1980.50.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Discriminated Rearing-Avoidance in Rats with Hippocampal Lesions

Abstract: Effects of bilateral hippocampal lesions were investigated in a newly developed discriminated rearing-avoidance task. A significant facilitation of avoidance conditioning was found in rats with hippocampal lesions. The over-all escape topography of the hippocampal-lesioned rats was mostly jumping whereas that of the controls was rearing. These findings suggest that the hippocampal lesion increases reactivity to shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…An interpretational difficulty of the above study is that the hippocampus is not necessary for learning of the active-avoidance task; in fact, hippocampal lesions or NMDA-receptor antagonists can facilitate active-or passive-avoidance learning, respectively (Mondadori et al 1989, Nadel 1968, Ohki 1982, Shimai & Ohki 1980. Thus increases observed in perforant-path responses that parallel learning may reflect ancillary learning of other aspects of the CS, such as context .…”
Section: Does Learning Produce Ltp-like Changes?mentioning
confidence: 93%
“…An interpretational difficulty of the above study is that the hippocampus is not necessary for learning of the active-avoidance task; in fact, hippocampal lesions or NMDA-receptor antagonists can facilitate active-or passive-avoidance learning, respectively (Mondadori et al 1989, Nadel 1968, Ohki 1982, Shimai & Ohki 1980. Thus increases observed in perforant-path responses that parallel learning may reflect ancillary learning of other aspects of the CS, such as context .…”
Section: Does Learning Produce Ltp-like Changes?mentioning
confidence: 93%
“…Hippocumpal Lesions: Facilitation of' Avoidance Beliavior Shimai and Ohki (1980) state that because of the paucity of variation in situations used in avoidance conditioning with the rat, it is difficult to find conclusive support for any hypothesis regarding the effects of hippocampal lesions upon avoidance conditioning. For example, they mention that some authors (Lovely, 1975;Schmaltz & Giulian, 1972) have found that hippocampal lesions facilitate the performance of two-way active escape and lever-press avoidance tasks, in the rat, while the same lesions cause an impairment in passive avoidance and one-way avoidance tasks (de Castro & Hall, 1975;Klein, Murphy, & Freeman, 1975).…”
mentioning
confidence: 99%
“…For example, they mention that some authors (Lovely, 1975;Schmaltz & Giulian, 1972) have found that hippocampal lesions facilitate the performance of two-way active escape and lever-press avoidance tasks, in the rat, while the same lesions cause an impairment in passive avoidance and one-way avoidance tasks (de Castro & Hall, 1975;Klein, Murphy, & Freeman, 1975). In order to investigate the nature of hippocampal function, Shimai and Ohki (1980) studied the effects of bilateral hippocampal lesions upon a discriminated, rearing avoidance task, in the rat.…”
mentioning
confidence: 99%